The Physical Properties of Erbium-Doped Yttrium Iron Garnet Films Prepared by Sol-Gel Method. (6th July 2011) - Shaiboub, Ramadan; Ibrahim, Noor Baa'yah; Abdullah, Mustafa; Abdulhade, Ftema
Abstract : Er x Y 3 - x Fe 5 O 12 nanoparticle films (x = 0.0, 0.6, 1.2, 2.0, and 2.5) have been synthesized by a sol-gel technique. All of the samples were annealed at 1000 ° C. The nanostructures were characterized by an X-ray diffractometer (XRD), the magnetic properties and the grain size were studied using a vibrating sample magnetometer (VSM), and a field emission scanning electron microscope (FE-SEM), respectively. The XRD patterns of the films show single phase structure. The sizes of the particles are in the range of 78 to 89 nm. The VSM result shows that the saturation magnetization of Er x Y 3 - x Fe 5 O 12 films decreased with the increment of Er concentration (x ).